ANALISIS POTENSI PENGEMBANGANGAN PERIKANAN BUDIDAYA IKAN AIR TAWAR DI KABUPATEN MIMIKA - Hasmiati Tejo; Tharsisius Pabendon (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2022)
This study aims to determine the potential for the development of freshwater fish aquaculture. The research method used is descriptive research method, which is a research method that describes or describes something, such as circumstances, conditions, situations, events, activities, and others. In this study, the data collection methods used were the observation method, the interview method, the questionnaire method, and the documentation method. To find out the strategy for developing freshwater aquaculture, the analytical instrument used in this study is an analysis of the current situation, namely the SWOT analysis. The results of this study indicate that the position of potential development of freshwater aquaculture lies in opportunity (quadrant) III, which means this area faces a large market opportunity but on the other hand faces several internal constraints/weaknesses, the focus of this strategy is to minimize internal problems, so as to seize better opportunities.